Varovanje dediščine v Triglavskem narodnem parku v razcepu med strokovnimi načeli, zakonodajo in vsakdanjo realnostjo - Hazler, Vito (Traditiones (Ljubljana), 2013)
This study of the state of immovable cultural heritage in Triglav National Park is based on publically available official lists from the Slovenian cultural heritage registry and years of fieldwork by the author. The area contains many important cultural heritage units that have contributed to the prominence of the park, including farm layouts, mountain pasture architecture, double hayracks in Bohinj, and other older structures that testify to people's close connection with the natural environment.
Keywords: ethnology; Kulturna dediščina; folk culture; Naravna dediščina; Narodni parki; cultural heritage; natural heritage; Zakonodaja; Triglavski narodni park; Etnologija; Ljudska kultura; Slovenska ljudska kultura; Spomeniško varstvo; Triglav National Park